Implementasi Perizinan Usaha Simpan Pinjam Koperasi Pasca Peraturan Menteri Koperasi dan Usaha Kecil Menengah Nomor 11 Tahun 2018 (Studi kasus di Kecamatan Blahbatuh Kabupaten Gianyar) - I Gusti Agung Ngurah Anom Deva; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2022)
Cooperatives are legal entities that run businesses based on the principle of kinship. In running a cooperative business, it must have a business license that functions as business legality and as a legal base in implementing it. The purposes of this study are to analyze the completeness of the requirements for a savings and loan business license for cooperatives in Blahbatuh sub-district, Gianyar Regency and the effectiveness of implementing savings and loan business permits for cooperatives in Blahbatuh sub-district, Gianyar Regency. This research method is an empirical legal research method with a sociological approach. Data collection techniques were carried out by interviewing respondents in the field. The sources of law used are primary and secondary sources of law. After the data was collected, it was then analyzed using descriptive data analysis techniques. The findings reveal that the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 11 of 2018 concerning Cooperative Savings and Loans Business Licensing. Based on the requirements for the completeness of a business license in carrying out a savings and loan activity in Blahbatuh District, Gianyar Regency, there are 44 cooperatives that already have a savings and loan business license and 79 cooperatives that do not have a savings and loan business license, there are factors that influence cooperatives in having a savings and loan business license, namely internal factors and external factors.